The Role of Training in Human Resource Management to Improve the Quality of School Administration - Nisa, Shofiyah Izzatun; Walid, Muhammad; Triwiyanto, Teguh (Proceedings Series of Educational Studies, 2024)
This article discusses the role of training in managing Human Resources (HR) in schools and its impact on the quality of administration. Through a qualitative research method with a literature study approach, this study identified four main outcomes: (1) improved administrative skills that support task effectiveness; (2) positive impact of training on the motivation and performance of administrative personnel; (3) effectiveness of data-based decision-making; and (4) improved team coordination and interdepartmental communication. The findings suggest that training improves technical skills and creates a more harmonious and productive work environment. This article is expected to provide insights for school managers and administrative staff in optimizing HR management to improve the quality of education.